Effects of renin gene transfer on blood pressure and renin gene expression in a congenic strain of Dahl salt-resistant rats. - St Lezin, E M (1996)
To investigate whether a BP-regulatory locus exists in the vicinity of the renin locus on rat chromosome 13, we transferred this chromosome segment from the Dahl salt-sensitive (S) rat onto the genetic background of the Dahl salt-resistant (R) rat. In congenic Dahl R rats carrying the S renin gene and fed an 8% salt diet, systolic BP was significantly lower than in progenitor Dahl R rats: 127 +/- 1 mmHg versus 138 +/- 4 mmHg, respectively (P < 0.05). Moreover, the decreased BP in the congenic Dahl R strain was associated with decreased kidney renin mRNA and decreased plasma renin concentration. These findings demonstrate that the Dahl S strain carries alleles in or near the renin locus that confer lower plasma renin concentration and lower BP than the corresponding alleles in the Dahl R strain, at least when studied on the genetic background of the Dahl R rat and in the environment of a high salt diet. The occurrence of coincident reductions in kidney renin mRNA, plasma renin concentration, and BP after interstrain transfer of naturally occurring renin gene variants strongly suggests that genetically determined variation in renin gene expression can affect BP.